A UNIFIED EMPIRICAL MODEL FOR INFRARED GALAXY COUNTS BASED ON THE OBSERVED PHYSICAL EVOLUTION OF DISTANT GALAXIES - Bethermin, M; Daddi, E; Magdis, G; Sargent, M; Hezaveh, Y; Elbaz, D; Le Borgne, D; Mullaney, J; Pannella, M; Buat, V; Charmandaris, V; Lagache, G; et al. (2012)
We reproduce the mid-infrared to radio galaxy counts with a new empirical model based on our current understanding of the evolution of main-sequence (MS) and starburst (SB) galaxies. We rely on a simple spectral energy distribution (SED) library based on Herschel observations: a single SED for the MS and another one for SB, getting warmer with redshift. Our model is able to reproduce recent measurements of galaxy counts performed with Herschel, including counts per redshift slice. This agreement demonstrates the power of our 2-Star-Formation Modes (2SFM) decomposition in describing the statistical properties of infrared sources and their evolution with cosmic time. We discuss the relative contribution of MS and SB galaxies to the number counts at various wavelengths and flux densities. We also show that MS galaxies are responsible for a bump in the 1.4GHz radio counts around 50 μJy. Material of the model (predictions, SED library, mock catalogs, etc.) is available online. © © 2012. The American Astronomical Society. All rights reserved..